Public Epistemic Authority Normative Institutional Design for EU Law - Laux, Johann Moritz (Mohr Siebeck, 2022)
Every court claims authority. Normative scholars assess the legitimacy of those claims. Public Epistemic Authority provides a new perspective on this task by drawing on mechanisms of collective intelligence and comparing courts reliability as decision-makers to that of other branches of government.
PublicationDate: 20220630
Keywords: Rom-Verordnungen -- Legitimacy -- PACS -- prediction -- machine learning -- democracy -- Collective Intelligence; -- Wisdom of the Crowds -- Cognitive Diversity -- Lehre von der objektiven Zurechnung -- Rechtsphilosophie -- Rechtstheorie -- Verfassungsrecht und Staatslehre -- Verwaltungsrecht -- Europarecht